Coronary Vasospasm While Treating Supraventricular Tachycardia: Is Adenosine Really to Blame? - Henry C. Quevedo; Jerson Munoz-Mendoza; Veronica Pinto Miranda; Rafael F. Sequeira (Case Reports in Cardiology)
Coronary artery spasm has been reported during adenosine stress testing. Herein, we describe a transient ST-segment elevation following adenosine therapy for supraventricular tachycardia. A 38-year-old male presented to the emergency department with palpitations. Electrocardiogram showed supraventricular tachycardia with short RP interval. Vagal maneuvers were unsuccessful. Adenosine was then administered in two successive injections of 6 and 12 mg dosages, respectively. A subsequent 12-lead electrocardiogram revealed ST-segment elevation in inferior leads with reciprocal changes. Coronary angiography disclosed nonobstructive coronary disease. A postprocedure electrocardiogram exhibited normal sinus rhythm with nonspecific T wave abnormalities. Cardiac biomarkers were elevated with a peak troponin I of 0.32. Echocardiogram depicted bicuspid aortic valve and normal systolic function. Electrophysiological study revealed a concealed left accessory pathway and successful radiofrequency ablation was performed. Given the dynamic changes in the electrocardiogram, we hypothesize that this event was most likely a coronary vasospasm. The mechanism of coronary spasm following adenosine injection remains uncertain. Potential mediators include channels and adenosine-2 receptors.